Secondary School Teachers’ Experiences in the Teaching of Accounting: A South African Perspective - Mohammed Xolile Ntshangase; Nkarhi Excellent Mathebula (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2026)
Persistent changes plague accounting as a subject because of shifts in the discipline originating from the developments in the profession. This study focuses on teachers' experiences in teaching accounting during curriculum change. It adopts an interpretive qualitative case study design to thoroughly understand accounting teachers' experiences. Semi-structured interviews with nine purposefully chosen accounting teachers from six schools and reflective journals were used to collect data. The findings indicated that Accounting teachers often struggle to teach new content as learners lack the adequate background knowledge to learn Accounting in succeeding grades. The unique language of the subject, shortage of textbooks and insufficient assessment activities in the textbooks constrained the teaching of Accounting. In addition, school management and Accounting specialists were found wanting in terms of the support offered to teachers and providing regular advisory services because of insufficient knowledge of the subject and inadequate supervision skills. The study recommended that heads of departments should be fully trained on curriculum changes in their subjects to provide guidance and supervise teachers under their leadership. On-going support should be provided by school subject advisors to assist teachers with challenging topics and teaching strategies.